Engineering microbial living therapeutics - Pedrolli, Danielle B. [UNESP]; Ribeiro, Nathan V. [UNESP]; Squizato, Patrick N. [UNESP]; Cozetto, Daniel A. [UNESP]; De Jesus, Victor N. [UNESP]; Freire, Paulo J.C. [UNESP]; Lins, Milca R.C.R. [UNESP]; Correa, Graciely G. [UNESP] (Elsevier, 2019)
A vast microbial community lives on and within the human body. Recent advances in microbiome studies have shown how some living bacteria can positively influence human health. The findings have raised interest in engineering indigenous human microbes to produce and deliver vaccines, drugs, and immunomodulators directly in or on the patient’s body, targeting a range of human diseases. Engineered living microorganisms are the next generation of therapeutics, programmed to diagnose and treat infections, tumors, metabolic disorders, and neurological diseases. This disruptive treatment approach is now nearing the clinic. This chapter will cover the most recent synthetic biology tools and approaches for engineering microbes as living therapeutics. Moreover, some technical and safety issues will be addressed.
Keywords: Designer probiotics; Drug delivery; Engineered microorganisms; Human microbiome; Living therapeutics; Synthetic biology